Patellar tendon structure responds to load over a 7-week preseason in elite male volleyball players - Rabello, L. M.; Zwerver, J.; Stewart, R. E.; van den Akker-Scheek, I.; Brink, M. S. (Scandinavian Journal of Medicine & Science in Sports, 2019)
The purpose of this study was to investigate the relation between external and internal load and the response of the patellar tendon structure assessed with ultrasound tissue characterization (UTC) in elite male volleyball players during preseason. Eighteen players were followed over 7 weeks, measuring four load parameters during every training and match: volume (minutes played), rating of perceived exertion (RPE) (ranging from 6 to 20), weekly load (RPE*volume), and jump frequency (number of jumps). Patellar tendon structure was measured biweekly using UTC, which quantifies tendon matrix stability resulting in four different echo types (I-IV). On average, players spent 615 min/wk on training and matches with an RPE of 13.9 and a jump frequency of 269. Load evaluation shows significant changes over the 7 weeks: Volume and weekly load parameters were significantly higher in week 3 than week 7 and in week 4 than week 2. Weekly load performed in week 4 was significantly higher than week 7. No significant changes were observed in tendon structure. On the non-dominant side, no significant correlations were found between changes in load parameters and echo types. At the dominant side, a higher weekly volume and weekly load resulted in a decrease of echo type I and a higher mean RPE in an increase of echo type II. The results of this study show that both external and internal load influence changes in patellar tendon structure of elite male volleyball players. Monitoring load and the effect on patellar tendon structure may play an important role in injury prevention.